2006
DOI: 10.1111/j.1600-0714.2006.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the jaws in patients treated with bisphosphonates – histomorphologic analysis in comparison with infected osteoradionecrosis

Abstract: We conclude that Actinomyces is involved in the chronic, non-healing inflammatory processes as a characteristic feature of both diseases. Together with the associated presence of increased osteoclast numbers, we suggest that both factors may be involved in osteolytic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
188
2
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(211 citation statements)
references
References 20 publications
5
188
2
13
Order By: Relevance
“…The abnormal oral epithelial hyperplasia referred to as pseudoepitheliomatous hyperplasia (PEH) was reported in 60% of human ONJ biopsy specimens (24,31) and was associated with the more aggressive ONJ phenotype with necrotic bone exposure. Akilov et al (41) reported the development of PEH in mouse ear skin by the injection of TNF-␣ and IFN-␥, suggesting that overproduction of Th1 cytokines in the barrier immunity stimulated the unregulated proliferation and migration of epidermal basal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abnormal oral epithelial hyperplasia referred to as pseudoepitheliomatous hyperplasia (PEH) was reported in 60% of human ONJ biopsy specimens (24,31) and was associated with the more aggressive ONJ phenotype with necrotic bone exposure. Akilov et al (41) reported the development of PEH in mouse ear skin by the injection of TNF-␣ and IFN-␥, suggesting that overproduction of Th1 cytokines in the barrier immunity stimulated the unregulated proliferation and migration of epidermal basal cells.…”
Section: Discussionmentioning
confidence: 99%
“…At the small distal root areas, where the oral mucosa wound was closed based on gross observation, histological evaluations revealed definitive bone exposure facilitated by the abnormal migration of oral epithelial cells. The abnormal proliferation and migration of epithelial cells resembling pseudoepitheliomatous hyperplasia (24,31) resulted in direct epithelial contact with the partially necrotic alveolar bone. Reduced new bone formation was noted in the extraction socket, and densely localized inflammatory cell infiltration was observed on the surface of the palatal bone adjacent to the tooth extraction site (Fig.…”
Section: Onj-like Lesions In Wtmentioning
confidence: 99%
“…It has also been proposed that NBPs may have an antiangiogenic effect, reducing blood flow and thus inducing bone cell necrosis and apoptosis [10,11]. One alternative explanation is an "outside-in" process in which mucosal damage provides oral bacteria with access to the underlying bone, leading to bone infection and necrosis [12]. NBP soft tissue toxicity would thus be the trigger leading to necrosis of the mucosa and bone [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of these lesions is not known. Although it is hypothesized that reduced bone turnover is the cause of this problem, reduced bone turnover has not been demonstrated in these patients, and bone scans suggested increased bone turnover at the affected sites (56,57). If there is an association of jaw osteonecrosis with oral bisphosphonate therapy, the incidence is very low.…”
Section: Osteonecrosis Of the Jawmentioning
confidence: 94%